Microbial vs thermogenic gas hydrates in the South Falkland Basin: BSR distribution and fluid origin. (April 2019) - Foschi, M.; Paganoni, M.; Cartwright, J.A.; Idiz, E.
Abstract: The South Falkland Basin hosts a working petroleum system, as well as one of the most recently discovered gas hydrate provinces of the South Atlantic Ocean. Using three-dimensional reflection seismic data, a series of bottom-simulating reflections (BSRs) are interpreted within two contrasting settings, (1) the thrust-cored anticlines, developed by the oblique convergence of the Scotia and the South American plates, and (2) the foreland basin, formed to the north of this plate boundary. These BSRs are interpreted as the base of the gas hydrate stability zone, and are associated with seismic indicators of underlying free-gas accumulations and overlying hydrate-bearing sediments. In the foreland basin, the BSR is laterally continuous for tens of kilometres, whereas in the fold belt, BSR occurrences are restricted to limited portions of the thrust-cored anticline crests. These observations, calibrated with sedimentological analyses and gas geochemistry, argue that the gas source for the gas hydrates within the thrust-cored anticlines is unrelated to in-situ microbial generation of methane, but instead is associated with the vertical seepage of thermogenic fluids from deeper cores of the anticlines. In contrast, the nature of the sediments in the foreland basin appears more favourable for the generation of shallow microbial methane. This study highlights that, in specific tectonic and depositional environments, the character of the BSR observed on reflection seismic data with the limited support of in-situ data, can be used to predict the most likely source of natural gas hydrate systems. Highlights: The South Falkland Basin hosts one of the most recently discovered gas hydrate provinces of the south Atlantic Ocean. Thermogenic and microbial gas produce contrasting and diverse gas hydrate deposits. The distribution of the BSR can be sufficient to understand the origin of the gas sourcing the formation of gas hydrates.